2008
DOI: 10.1073/pnas.0808230105
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optical properties of chemical vapor deposited single crystal diamond by low-pressure/high-temperature annealing

Abstract: Single crystal diamond produced by chemical vapor deposition (CVD) at very high growth rates (up to 150 m/h) has been successfully annealed without graphitization at temperatures up to 2200°C and pressures <300 torr. Crystals were annealed in a hydrogen environment by using microwave plasma techniques for periods of time ranging from a fraction of minute to a few hours. This low-pressure/high-temperature (LPHT) annealing enhances the optical properties of this high-growth rate CVD single crystal diamond. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 28 publications
(52 reference statements)
6
89
0
Order By: Relevance
“…A smaller nitrogen content at higher temperature is plausible due to the higher nitrogen fugacity associated with higher temperature. It has been reported that the low-pressure/high-temperature annealing in a hydrogen environment can significantly enhance the optical properties of chemical vapor deposition (CVD) single-crystal diamond (19). We suggest that the similar treatment might apply to nanopolycrystalline diamond.…”
Section: Resultsmentioning
confidence: 83%
“…A smaller nitrogen content at higher temperature is plausible due to the higher nitrogen fugacity associated with higher temperature. It has been reported that the low-pressure/high-temperature annealing in a hydrogen environment can significantly enhance the optical properties of chemical vapor deposition (CVD) single-crystal diamond (19). We suggest that the similar treatment might apply to nanopolycrystalline diamond.…”
Section: Resultsmentioning
confidence: 83%
“…The emission lines at 2.313 eV (535.9 nm) and 2.153 eV (575 nm) have been observed previously in some natural brown diamonds and can also be produced in diamonds containing nitrogen (mainly in the B form) by radiation damage and annealing at high temperature. Vibronic system with 2.153 eV (575 nm) ZPL corresponds to the [N-V] 0 [15]. The 2.024 eV (613 nm) center can be observed in some natural type I diamonds.…”
Section: 3mentioning
confidence: 99%
“…In the hydrogen-related absorption bands, the ∼3107 cm −1 absorption peak is attributed to the stretching vibration of vinylidene group (>C=CH 2 ), the ∼2923 cm −1 , ∼2854 cm −1 peaks are due to the asymmetrical and symmetrical stretching vibration of sp 3 -hybridized C-H bonds [13][14][15], and the 3762 cm −1 and ∼3660 cm −1 peaks are, respectively, related to the stretching vibration of hydroxyl group and H 2 O. Comparing the FTIR spectra of the EFPCDs (Figures 3(a) and 3(b)) with those of the ARPCDs (Figures 3(c) and 3(d)), we find that the intensity of hydrogen-related absorption peaks of the ARPCDs is stronger than that of the EFPCDs, especially the ∼2923 cm −1 and ∼2854 cm −1 peaks are very weak in the FTIR spectra of the EFPCDs.…”
Section: Fourier Transform Infrared Spectroscopymentioning
confidence: 99%
“…Generally, the gemologists have begun to enhance the color of diamond since the 1930s [2] and diamond treatments in the modern era mostly involve high-energy irradiation, high pressure and high temperature (HPHT) treatment, low pressure and high temperature (LPHT) annealing, and combination of these treatments [3][4][5][6][7][8][9][10][11]. Such as Vins [12] reported that natural diamonds with brown hue could be altered to display purple to red color, through multiprocess treatments including HPHT treatment (6-7 GPa at over 2150°C), high-energy irradiation, and LPHT annealing (lower than 1100°C).…”
Section: Introductionmentioning
confidence: 99%